Human papillomavirus genotype spectrum in Czech women: Correlation of HPV DNA presence with antibodies against HPV-16, 18, and 33 virus-like particles - Tachezy, R.; Hamšíková, E.; Hájek, T.; Mikyšková, I.; Šmahel, M.; Van Ranst, M.; Kaňka, J.; Havránková, A.; Rob, L.; Guttner, V.; Slavík, V.; Anton, M.; et al. (Journal of medical virology, 1999)
Because the biological spectrum of human papillomavirus (HPV) genotypes present in cervical cancer lesions varies according to the geographical region studied, and because little genotype information is available for Central and Eastern European countries, we studied the endemic HPV‐genotype spectrum in cervical samples collected from women visiting gynaecological departments of selected hospitals in the Czech Republic. In a series of 389 samples, 171 (44.0%) were positive for HPV DNA using a consensus‐primer polymerase chain reaction (PCR). Genotyping of the HPV PCR products was done using dot‐blot hybridisation with type‐specific oligonucleotide probes and thermocycle DNA sequencing. Twenty‐two different HPV types were detected, HPV‐16 being the most prevalent type irrespective of severity of the lesions (55.0%). Multiple HPV types were found in 16.4% of our HPV‐DNA‐positive samples. The prevalence of HPV infection was 23.0% in women with normal findings and 59.4% in patients with cervical neoplasia, and increased significantly with the severity of the disease: 52.9% in low‐grade lesions, 58.0% in high‐grade lesions, and 73.5% in cervical carcinomas (P for trend < .00001). In the sera of 191 subjects, 89 with normal findings and 102 with different forms of cervical neoplasia, the prevalence of HPV‐specific IgG antibodies was tested by an enzyme‐linked immunosorbent assay (ELISA) using virus‐like particles (VLPs) of HPV‐16, ‐18, and ‐33. Antibodies were significantly more prevalent in HPV‐DNA‐positive than in HPV‐DNA‐negative women and there was no association with age. In agreement with the results of HPV genotyping, antibodies reactive with HPV‐16 VLPs were the most frequent and, moreover, their prevalence increased with the cervical lesion severity. About half of the subjects with smears in which either HPV‐16 or HPV‐33 DNA had been detected possessed antibodies reactive with homotypic VLPs. With HPV‐18‐DNA‐positive subjects, however, fewer than 25% displayed homotypic antibodies. In general, subjects older than 30 years of age had antibodies reactive to HPV‐specific VLPs more often than subjects younger than 30 years of age. In women with benign findings, the seropositivity to HPV‐16, ‐18, and ‐33 VLPs increased with age, whereas in women with cervical neoplasia the seropositivity decreased with age. J. Med. Virol. 58:378–386, 1999. © 1999 Wiley‐Liss, Inc.